Creativity and Innovation in Culinary Business: Systematic Literature Review (SLR) Approach - Endang Kustami; Muzakar Isa; Kussudyarsana (JURNAL ILMIAH EDUNOMIKA, 2025)
This study analyzes recent research trends and thematic focuses on creativity and innovation within the culinary business, synthesizing findings from six key journal articles. The analysis identifies six major themes driving creativity and innovation in this context. First, cultural creativity emphasizes leveraging local heritage and traditions to differentiate culinary offerings and foster place-based identity. Second, sustainability and green practices highlight the importance of integrating environmentally friendly strategies to enhance competitive advantage. Third, behavioral psychology explores how traits such as motivation, locus of control, and self-efficacy influence entrepreneurial creativity and success. Fourth, digital transformation emerges as a critical enabler of innovation, with the adoption of digital tools, e-commerce platforms, and social media enhancing operational efficiency and customer engagement. Fifth, market orientation underscores the role of proactive consumer-centric approaches, supported by advanced technologies and data-driven insights, in driving innovative culinary solutions. Finally, resourceful financial management demonstrates how financial bootstrapping fosters creative problem-solving, particularly among small and medium-sized enterprises (SMEs) with limited resources. The findings suggest that creativity and innovation in the culinary business are shaped by an intersection of cultural, psychological, technological, and financial factors. Sustainability and digital adoption are particularly highlighted as key drivers of differentiation and competitiveness. This synthesis provides a comprehensive framework for understanding how culinary businesses adapt to evolving consumer demands, market competition, and societal trends. Future research should further explore the integration of these themes to support the development of innovative and resilient culinary enterprises.